PENGARUH TATA GUNA LAHAN TERHADAP FLUKTUASI DEBIT EMBUNG KAMPUNG BANJAR DI WILAYAH PERKANTORAN PROVINSI KALIMANTAN SELATAN - Mahmud Mahmud; Ahmad Kurnain; Rizqi Puteri Mahyudin; Fitria Hutabarat (EnviroScienteae, 2022)
This study was conducted to find out  the value of the drainage coefficient of the office area in South Kalimantan under the existing conditions, the effect of land use changes on fluctuations in discharge at Embung Kampung Banjar and the green open space that must be available with the existence of Embung Kampung Banjar. The existence of Embung Kampung Banjar is expected to reduce the impact of excessive rainfall which causes various kinds of natural disasters. This study usesd the Rational Method analysis to get the value of rainfall intensity in determining the planned discharge, the method of analysis of the coefficient of flow and the research method used for discharge fluctuations in Embung Kampung Banjar that is simulated with the synthetic unit hydrograph ITB –2 Kirpich, Snyder and Mononobe which all calculations by useng Microsoft Excel . The results shows that the simulation of land use change by adding the area of residential housing and offices are evidence of reduced open areas. The calculation of the maximum discharge coefficient of the existing flow using the Synthetic Unit Hydrograph (HSS) ITB 2 Timelag Kirpich of 7.83 m3/s and the results of flood tracking caused a decrease in peak discharge of 5.4 m3/s the largest land use change was found in the flow coefficient is 0.499 with a maximum discharge of 9.69 m3/s where the housing area is 0.85 km2 and offices are 0.47 km2. In Indonesian Law Number 26 of 2007 on Spatial Planning Article 29 paragraph 3 regarding the proportion of Green Open Space (RTH) about 20 percent of the city area. The calculation results of the peak discharge capacity of Embung Banjar Kampung which is equal to 6.8963 m3/s equal to 15 percent of the flow area of Embung Kampung Banjar which is obtained from the maximum discharge calculation, which is 9.69 m3/s. Then the results of the routing flood that caused a decrease in the discharge amounted to 6.6 m3/s, so the overall result is that the reservoir is still safe if overflow occurs in the reservoir.